2021
DOI: 10.1186/s13014-021-01925-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a radiomics-based model to predict local progression-free survival after chemo-radiotherapy in patients with esophageal squamous cell cancer

Abstract: Purpose To develop a nomogram model for predicting local progress-free survival (LPFS) in esophageal squamous cell carcinoma (ESCC) patients treated with concurrent chemo-radiotherapy (CCRT). Methods We collected the clinical data of ESCC patients treated with CCRT in our hospital. Eligible patients were randomly divided into training cohort and validation cohort. The least absolute shrinkage and selection operator (LASSO) with COX regression was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…But, PET/CT examination was highly expensive than CT or MRI and the sample was small in the study. Luo et al [ 23 ] also developed a nomogram model for predicting local PFS based on CT images and C-index was 0.723 in test cohort. This study included clinical response to develop model and obtained a fine result.…”
Section: Discussionmentioning
confidence: 99%
“…But, PET/CT examination was highly expensive than CT or MRI and the sample was small in the study. Luo et al [ 23 ] also developed a nomogram model for predicting local PFS based on CT images and C-index was 0.723 in test cohort. This study included clinical response to develop model and obtained a fine result.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram yielded a C-index of 0.72 (95% CI 0.70–0.75) in the validation cohort, which was significantly better than those derived from a radiomics signature or the clinical nomogram alone ( p < 0.0001 for each comparison) [ 33 ]. Luo et al also developed and validated a model based on pretreatment CT radiomics features and clinical parameters to predict PFS [ 34 ]. Using 17 radiomics features, the nomogram in that study demonstrated a C-index of 0.72 (95% CI 0.65–0.79) in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the individual features integrated into the optimal subset belong to 5 (out of 7) feature families with only shape and NGTDM being excluded. Although this does not denote that usable information cannot be extracted from the latter categories, it implies decreased differential characteristics compared to the other feature families that could result from tumor shape irregularities, high variance and reduced neighboring gray level difference [ 44 ]. Nonetheless, the GLCM feature family includes the “Difference Variance”, “Maximum Probability”, “Correlation” (selected in both CTV and PG ROIs) and “Cluster Prominence” features, suggesting distinct aspects of spatial gray-level variation within local neighbors on a pixel basis.…”
Section: Discussionmentioning
confidence: 99%